(untitled) (Annals of Medical Research, 2021)
Aim: Cone-beam computed tomography is an important diagnostic tool in dentistry. However, cone-beam computed tomography technology has various limitations such as image artifacts. The aim of this study was to evaluate the incidence of various artifacts or errors in the cone-beam computed tomography images and to investigate the correlation between artifacts and parameters such as age groups, gender, imaging areas and acquisition times.Material and Methods: Five different types of artifacts were evaluated. Patient’s age, gender, the reason for radiographic examination, the field of view (FOV), acquisition time, anatomical area and presence of artifacts were recorded. The Pearson Chi-Square and Fisher’s Exact test were used for comparisons of the parameters.Results: The images of 600 patients aged from 6 to 88 years (mean age ± standard deviation: 36.2 ±16.8) were examined. The beam hardening (dark band or streaks) were the most common artifacts (38.8%). An increase in the number of artifacts was observed with the increase in FOV and voxel size (p0.05). The prevalence of motion artifacts was 0.7% and a statistically significance was found between motion artifact and age. (p0.05). The cupping and aliasing artifacts were also correlated with the FOV. Conclusion: The results of our study showed that artifacts are an important problem affecting image quality. Careful patient positioning and the optimum selection of scan parameters are the most important factors in preventing image artifact.